New insights on glycerol transport in Saccharomyces cerevisiae - Neves, Luísa (2004)
Previous studies evidenced in Saccharomyces cerevi-siae the activity of a H þ /glycerol symport, derepressed by growth on non-fermentable carbon sources, later associated with GUP1 and GUP2 genes. It was also demonstrated that only the combined deletion of GUP1, GUP2 together with GUT1 (glycerol kinase) abolished active transport in ethanol-induced cells. In this work, we show that a glycerol H þ /symport, with identical characteristics to the previously described, was found in gup1gup2gut1 grown under salt-stress, particularly high in cells collected during diauxic-shift. These results suggest different roles for Gup1/2p than glycerol transport. The gene encoding for glycerol active uptake is thus yet unknown.